PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PT. PLN (PERSERO) APJ - Karomah, 12.05.51.0136 (Students' Journal of Economic and Management, 2017)
The purpose of this study was to analyze the influence of leadership style, motivation and discipline to employee performance PT. PLN (Persero) APJ. The population in this study were employees at PT. PLN (Persero) Area Network Maintenance numbering as many as 250 people. The sample in this study as many as 71 people. The sampling technique used purposive sampling. The criteria for the samples in this study are mployees who work more than 3 years. The analysis tool used is multiple linear regression. The results of the analysis can be concluded that: leadership style and significant positive effect on employee performance. Job motivation and significant positive effect on job satisfaction. Labor discipline and significant positive effect on employee performance. Keywords: leadership style, employee motivation, work discipline and employee performance